Заметки к переписке Н. М. Карамзина в контексте сравнительной литературы - Дуккон, Агнеш (SlavVaria, 2022)
The Notes to the Correspondence of N. M. Karamzin – In the Context of Comparative Literature. This paper treats the letters of N. M. Karamzin to I. I. Dmitriev, written between 1787 and 1826. The aim of the author is to investigate the connections of private life, literature and history in the correspondence of the two poets and point out the common motifs with the novel of the Hungarian writer, Mór Jókai Freedom under the snow (1879). The novel deals with the revolt of decabrists in 1825, in which the real hictorical figures, like tsar Alexander I and Pushkin, play an important role. The author of the paper comes to the conclusion that the similarities in the characters can be interpreted as the common spiritual attitude of Karamzin and Jókai, and in the other hand, as the Hungarian writer’s great interest in the Russian history and his profound knowledge in that area.